2021
DOI: 10.1021/acsaem.1c00917
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap between Small Molecular π-Interactions and Their Effect on Phenothiazine-Based Redox Polymers in Organic Batteries

Abstract: Organic redox polymers are considered a “greener” alternative as battery electrode materials compared to transition metal oxides. Among these, phenothiazine-based polymers have attracted significant attention due to their high redox potential of 3.5 V vs Li/Li+ and reversible electrochemistry. In addition, phenothiazine units can exhibit mutual π-interactions, which stabilize their oxidized states. In poly­(3-vinyl-N-methylphenothiazine) (PVMPT), such π-interactions led to a unique charge/discharge mechanism, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 61 publications
0
20
0
Order By: Relevance
“…In previously investigated PT-based polymers this behavior was caused by the (partial) dissolution of the polymer in the electrolyte in its oxidized form. [31,33,35] This also happened for PVAPT, as the photograph of the separator taken from a cell after CV measurement in Figure 3A shows, which is pink/purple-colored due to the presence of oxidized PVAPT. Cross-linked X-PVAPT as well as PSAPT and PSAPT-X-DVB, on the other hand, remained insoluble in the electrolyte even in their oxidized form (see photographs of separators in the respective CVs in Figure 3A).…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…In previously investigated PT-based polymers this behavior was caused by the (partial) dissolution of the polymer in the electrolyte in its oxidized form. [31,33,35] This also happened for PVAPT, as the photograph of the separator taken from a cell after CV measurement in Figure 3A shows, which is pink/purple-colored due to the presence of oxidized PVAPT. Cross-linked X-PVAPT as well as PSAPT and PSAPT-X-DVB, on the other hand, remained insoluble in the electrolyte even in their oxidized form (see photographs of separators in the respective CVs in Figure 3A).…”
Section: Resultsmentioning
confidence: 80%
“…A change in polymer backbone to poly(norbornenes) diminished both solubility and π-interactions and furnished attractive battery polymers, [34] while attaching sterically demanding groups (e. g., mesityl) to the phenothiazine units in PVMPT resulted in a low cycling stability due to a complete lack of π-interactions combined with a high electrolyte solubility of the oxidized polymers. [35] Most of these polymers had in common that the nitrogen atom of the phenothiazine groups was substituted with methyl. Changing this substituent alters the redox properties of phenothiazine, where aryl groups can enhance the stability of the phenothiazine radical cation and thereby the reversibility of the redox process.…”
Section: Introductionmentioning
confidence: 99%
“…One is changing the polymer backbone from vinyl to bulkier, such as norbornene (PNMPT) [ 165 ] and methylmaleimide (P(VMPT‐alt‐MM)) (see the chemical structures in Figure 11d). [ 166 ] The other is introducing a bulky substituent into the N ‐position of the PTZ unit (PV‐p‐TPT, PV‐o‐TPT, PVMesPT, and PVAnthPT in Figure 11e). [ 166 ] Such a series of studies clearly showed that the small changes in the chemical structure of ROMs could considerably influence the electrochemical performance by modulating the supramolecular interactions.…”
Section: Classification Based On Redox Centersmentioning
confidence: 99%
“…[ 166 ] The other is introducing a bulky substituent into the N ‐position of the PTZ unit (PV‐p‐TPT, PV‐o‐TPT, PVMesPT, and PVAnthPT in Figure 11e). [ 166 ] Such a series of studies clearly showed that the small changes in the chemical structure of ROMs could considerably influence the electrochemical performance by modulating the supramolecular interactions. Meanwhile, several other papers reporting PTZ‐based electrode materials have also been published.…”
Section: Classification Based On Redox Centersmentioning
confidence: 99%
“…We have intensively investigated phenothiazine-based redox polymers as positive electrode materials in recent years. , Due to the high reversibility and fast kinetics of the oxidation of the phenothiazine group, such polymers can show outstanding cycling stabilities and rate capabilities . Using aliphatic polymer backbones, however, the intrinsic conductivity in the polymer is low (transport through hopping processes), and thick electrodes with high mass loadings of active polymer are challenging to obtain.…”
Section: Introductionmentioning
confidence: 99%